Effects of short-term extreme temperature treatment on the development and reproductive capacity of Encarsia formosa - Li, Ming-Jiang; Zhang, Bo; Chen, Guo-Hua; Zhou, Shun-Wen; Liu, Ji-Huan; Lu, Mei; Zhang, Jin-Long; Yang, Shao-Wu; Zhang, Xiao-Ming (Frontiers in Physiology, 2023)
Encarsia formosa is a natural enemy of the invasive pest Bemisia tabaci and is known to be a dominant parasitic. The frequency and magnitude of climate extremes, particularly temperature extremes, have increased, which has put insect populations at risk. However, the effects of temperature extremes on E. formosa are not well understood. To examine the impact of short-term extreme temperature exposure on the development and reproduction of E. formosa, eggs, larvae, pupae, and adults were exposed to high/low temperature treatments (HLT25, HLT50, LLT25, and LLT50). Our findings indicate that the pupal stage of E. formosa exhibited the strongest tolerance to both heat and cold, while adults exhibited a weaker tolerance. The shortest egg-to-adult development period of 12.65 d was observed in E. formosa exposed to HLT50 treatment during the egg-larval stage. The parasitism peak of the adult stage was delayed by 1–6 d after exposure to extreme temperatures during the egg-larval stage. Conversely, the parasitism peak was advanced by 1–3 d after exposure to extreme temperatures during the pupal and adult stages. The eclosion rate, total parasitism, eclosion rate of the F1 generation, and adult longevity of the F1 generation were lower in the treatment groups than in the control groups. The F1 generation's development period was prolonged to 15.49 and 15.19 d after exposure to HLT25 and HLT50 treatments, respectively, during the egg-larval stage. The F1 generation's development period was shortened to 13.33 d after exposure to LLT50 treatment during the pupal stage. Male individuals appeared in the F1 generation after exposure to HLT50 treatment during the pupal stage, with females accounting for only 56.38%. Our results demonstrate that short-term exposure to extreme temperatures has detrimental effects on the growth and reproduction of E. formosa. In field biocontrol against E. formosa, the release of E. formosa should be avoided as much as possible when the ambient temperature is higher than 35 °C or lower than 0 °C. During extreme temperature conditions, timely supplementation and release of E. formosa population, along with ventilation and cooling in greenhouse facilities during summer, are necessary for better pest control efficacy.